Forecasting servise markеting determinants within the concept of the information society - Telnov, Anatolii; Reshmidilova, Svitlana (Edelweiss Applied Science and Technology, 2024)
The influence of information technologies on the development of service marketing and the transformation of traditional approaches to marketing tools in this field is substantiated in the article. It is highlighted that higher-quality services are demanded by consumers in a dynamic market environment. A scientific and methodological toolkit of heuristic forecasting involving highly qualified marketing experts is applied to forecast determinants in service marketing. The number of experts, the number of evaluated determinants, and the scoring system for their assessment are justified using a calculation method. Statistical indicators of service marketing determinants are calculated, their relative significance is assessed, paired comparison matrices are constructed, and scaling is performed following the proposed algorithm. This approach allowed the impact level of each determinant on service marketing to be determined and their ranking established. A sufficiently high level of agreement among experts is demonstrated through the calculation of expert opinion concordance coefficients. Predictive assessments of service marketing determinants are provided using the expert evaluation method, determining their degree of influence. Specific directions for improving engagement with the target audience and utilizing digital technologies in service marketing are formulated.